Otimização multivariada de extração de compostos bioativos em folhas, casca e resíduos de seiva de Croton lechleri - Diedrich, Camila (2018)
The natural plants of the Amazon have been instigating the interest of researchers to extract the products of the region. The purpose of this research focuses on no development of new drugs from bioactive plant compounds aimed at fighting numerous diseases associated with increased production of reactive oxygen species. The sap, leaves and barks of plants of the genus Croton are used by native Amazonian peoples for medicinal purposes with healing, anti-inflammatory and antibacterial action. This study aimed to optimize the extraction process of natural products from leaves, bark of C. lechleri extracts. The design for the extraction of natural compounds was performed by 2³ factorial experimental design and analysis using Response Surface Methodology (RSM). Three factors (independent variables); type of solvent (water or ethanol), extraction time (30 or 90 min) and extraction temperature (35 °C and 70 °C) were used for the experimental design. While the dependent variables; content of phenolic compounds, antioxidant activity by DPPH, and anthocyanin content were evaluated in extracts of C. lechleri. The composition of the diversity of phenolic compounds was investigated by high performance liquid chromatography. The data set was submitted to Principal Component Analysis (PCA). The best extraction condition of phenolic compounds was water, at 70 ºC for 30 min, while for the compounds with antioxidant activity was ethanol, at 70 ºC for 90 min. Chromatographic analysis revealed the presence of gallic acid, catechin, epicatechin, syringic acid, coumaric acid and ferulic acid. Finally, the factorial design allowed the reduction of the number of tests carried out without diminishing the quality of information and the results of analysis of variance. Response Surface Methodology and Principal Component Analysis proved to be efficient tools used to analyze data bioactivity of extracts from C. lechleri.